Pengaruh Pemberian Kombinasi Ekstrak Etanol Daun Sidaguri (Sida rhombifolia L.) dan Rimpang Jahe Merah (Zingiber officinale Rosc.) pada Mencit Jantan Hiperurisemia - Kinanthi Putri Rizki; Siti Muslichah; Indah Yulia Ningsih (Pustaka Kesehatan, 2018)
This study aimed to determine the effect of the combination of sidaguri leaves and red ginger rhizome extracts in uric acid levels of hyperuricemic male mice. Thirty-six mice were divided into nine groups including normal group, the positive control (+), negative control (-), extracts of four treatment groups with a variety of combinations and two groups of single extract. Hyperuricemia induction was performed by administering mixture melinjo 10% of the standard feed mice for 7 days dan potassium oxonate 250 mg/kg BB intraperitoneally at 2 hours before blood sampling. The results showed that the combination dose of sidaguri leaves of 50 mg/kg BB and red ginger rhizome 400 mg/kg BB had higher antihyperuricemia activity than other combinations in lowering uric acid levels of mice. Compounds may have antihyperuricemic activity were flavonoids, alkaloids, saponins, tannins, and terpenoids. Keywords: sidaguri leaves, red ginger rhizome, antihyperuricemic activity, uric acid